MODEL MATEMATIKA UNTUK MENGUKUR TINGKAT KEBASAHAN PADA SAAT HUJAN TURUN - Cristina Anjela Tamba; Leli Deswita; Supriadi Putra (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the mathematical models for measuring the degree of wetness caused by rain, which is a review of the Dank Hailman and Bruce Torrents article [Mathematics Magazine, 82: 266-277 (2009)]. Mathematical models are made with three diﬀerent body shapes, namely a rectangular shape, round shape, and ellipsoidal shape. From each model, the optimum speed can be determined, which minimizes the degree of wetness of the body.